PREDICTING THE ECONOMIC EFFICIENCY OF THE INTRODUCTION OF A SINGLE INFORMATION SYSTEM HEALTHCARE - Byelikova, I.V.; Katrushov, A.V.; Kostrikov, A.V.; Rudenko, L.A. (World of Medicine and Biology, 2013)
The modern period of development of a society characterized by rapid development of computer technology, they penetrate into all spheres of human life, that constitutes the global information space. The main priority for Ukraine is to build an inclusive and development-oriented information society. One of the main results of the introduction of information technology in medicine is saving working time of doctors. It is important to distinguish between economic efficiency for polyclinics and in hospital settings.In the ambulatory sector, above all, the economic benefit expected with decreasing circulation of paper documents.Savings are achieved by reducing search time and issue paper maps, epicrisis, test scores and more.It is important to conduct electronic registration of cases, the causes and the number of days of disability the patient. The registry sick leaves simultaneously simplify the monitoring of document flow and rates of disease with temporary disability.In the hospital sector as the basis of economic benefit is time saving, which reduces the period of hospitalization. Thorough and comprehensive fixing all conducted medical operations and of treatments will qualitatively carry out calculations and reduce unforeseen cash costs. It should be noted, economic efficiency in health care is not the primary indicator. But it helps in the prioritization of certain events.